Newborn Screening for Sickle Cell Disease: Results from a Pilot Study in the Portuguese Population - Diogo Rodrigues; Ana Marcão; Lurdes Lopes; Ana Ventura; Teresa Faria; Anabela Ferrão; Carolina Gonçalves; Paula Kjöllerström; Ana Castro; Sofia Fraga; Marta Almeida; Tabita Maia; et al. (International Journal of Neonatal Screening)
The Portuguese Newborn Screening Program currently includes 28 pathologies: congenital hypothyroidism, cystic fibrosis, 24 inborn errors of metabolism, sickle cell disease and spinal muscular atrophy. This pilot study for sickle cell disease newborn screening, including 188,217 samples, was performed between May 2021 and December 2023, with phase I, including 24,130 newborns, in the Lisbon and Setubal districts and phase II, including 164,087 newborns, in the whole country. DBS samples were analyzed through capillary electrophoresis. In phase I, a high birth incidence of sickle cell disease was found (1:928 NBs), resulting from the identification of 24 HbSS and 2 HbSC patients. This birth incidence decreased but remained significant when the pilot study for sickle cell disease newborn screening was expanded to a national level, with the identification of 67 sickle cell disease patients (59 HbSS and 8 HbSC), revealing a birth incidence of 1:2449 NBs. These data suggest that this condition is becoming increasingly relevant in Portugal, thus reflecting a general European trend, where sickle cell disease is already recognized as a public health problem. Therefore, it highlights the importance of its integration into the Portuguese National Newborn Screening Program panel in January 2024, thus allowing the early identification and clinical follow-up of these patients.